Ventricular ectopic activity after premature atrial beats in acute myocardial infarction. - Myerburg, R J (1977)
Ventricular ectopic activity occurred only after premature atrial beats in a patient with an acute inferior wall myocardial infarction. The ventricular ectopic activity occurred only when the coupling interval between the premature atrial beats and preceding sinus beat was less than or equal to 0-44 s. The sinus cycle length, however, appeared to influence the form of expression of ventricular ectopic activity independent of coupling intervals, with single premature ventricular contractions occurring at cycle lengths greater than or equal to 0-72 s, couplets at cycle lengths of 0-68 to 0-71 s, and ventricular tachycardia at cycle lengths less than or equal to 0-67 s.